Permainan Bolbakdor Untuk Pembelajaran Gerak Dasar Pada Siswa Kelas III (Department of Physical Education, Sport, Health and Recreation, 2015)
This research is a development research. The procedure which is used are: (1) conducting a product analysisthat will be developed which is obtained from the collection of information, including field observation andliterature review, (2) developing an early form of the product (in the form of BOLBAKDOR game), (3)validation test by the expert, that is one physical education, health and sports subject study expert and one physical education, (4) first product revision, product revision based on the result of expert’s evaluation and small scale trial (12 students). (5) trial on the field (26 students), (6) last product revision conducted based on the result of the trial, (7) the final result of BOLBAKDOR game toward third graders students which is resulting in the revision of the trial on the field. From the average result of the expert’s validation on the small-scale trial,percentage obtained at 81,33% (good). The student’s average questionnaire result on the small scale, percentage obtained at 89,02% (good). From the average result of expert’s validation on the field, percentage obtained at 82% (increased). Average result of the questionnaire on the field trial, percentage obtained at 91,71% (very good).